1988
DOI: 10.1093/ajcn/47.2.280
|View full text |Cite
|
Sign up to set email alerts
|

A WHO collaborative study on iron supplementation in Burma and in Thailand

Abstract: Studies on the treatment and prevention of iron deficiency anemia, in pregnant and nonpregnant women and in men, were conducted in Thailand and Burma. The effects of the dose of Fe, duration of Fe administration, additional supplementation with folate, mode of supplement delivery (either supervised or unsupervised), and the presence of Hb(AE) were studied. The frequency and severity of side effects were also recorded. Fe administration resulted in an increase in hemoglobin concentration in all anemic individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 6 publications
4
47
1
Order By: Relevance
“…The hemoglobin concentrations and serum ferritin concentrations of both Hb E and nonthalassemic groups declined after routine iron supplementation (Table 3). The different results obtained in our study compared with the previous study (19) are possibly due to the different times of measurement and globin genotypes of the subjects. In our study, the medians for the first and second measurements were 13 and 32 wk of gestation, respectively, whereas in the former study (19) the second measurement was done at 32-36 wk of gestation and globin genotype was not determined.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The hemoglobin concentrations and serum ferritin concentrations of both Hb E and nonthalassemic groups declined after routine iron supplementation (Table 3). The different results obtained in our study compared with the previous study (19) are possibly due to the different times of measurement and globin genotypes of the subjects. In our study, the medians for the first and second measurements were 13 and 32 wk of gestation, respectively, whereas in the former study (19) the second measurement was done at 32-36 wk of gestation and globin genotype was not determined.…”
Section: Discussioncontrasting
confidence: 97%
“…To our knowledge, there has been only one study conducted before in the northeastern part of Thailand that compared hemoglobin response to iron supplementation in pregnancy between normal hemoglobin type (Hb AA) and heterozygous Hb E (Hb EA) (19). In this previous study, a significant difference was observed in the rise of hemoglobin concentration between pregnant women with Hb AA and Hb EA after 15 wk of iron supplementation and subjects with Hb EA did not achieve the same hemoglobin concentration as those with Hb AA.…”
Section: Discussionmentioning
confidence: 99%
“…Three months of daily supplementation with 1 mg folic acid and multivitamin during the postpartum period produced slight, though signi®cant, increases in mean Hb and Hct levels (2 g l -1 and and 0.008, respectively) compared to multivitamin use alone among lactating American women 77 . However, no bene®t of folic acid supplementation on Hb response was observed in trials among either non-pregnant Thai women 67 or Malaysian adolescent girls 78 . In the latter study, however, plasma ferritin increased signi®cantly following supplementation with iron and folate, but decreased in the folate-alone group, suggesting that folate may have stimulated synthesis of Hb from existing iron stores.…”
Section: Folatementioning
confidence: 97%
“…2. May lessen the severity of anaemia of prematurity among young infants, although no large trials have 67 .…”
Section: Folatementioning
confidence: 99%
“…Compliance has been reported to be influenced by the undesirable side effects brought about by iron tablet intake, which are related to the amount, frequency and duration of intake, and form of the tablets (Charoenlarp et al, 1988;Aguayo et al, 2005). Side effect is dose related as seen in studies conducted among Malaysian adolescent girls (Tee et al, 1999) and Bangladeshi pregnant women (Hyder et al, 2002).…”
Section: Discussionmentioning
confidence: 99%